2007
DOI: 10.1210/me.2006-0465
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Novel Rac/RhoA Guanosine Triphosphatase-Nuclear Factor-κB Inducing Kinase Signaling Pathway Mediating Angiotensin II-Induced RelA Transactivation

Abstract: Angiotensin II (Ang II) is the major effector peptide of the renin angiotensin system that induces inflammatory gene expression through the nuclear factor-kappaB (NF-kappaB) transcription factor. Activation of latent cytoplasmic NF-kappaB is controlled by distinct pathways, the best known being the canonical pathway controlling IkappaB kinase activation. Interestingly, Ang II only weakly activates the canonical pathway. Although basal nucleocytoplasmic RelA shuttling is required for Ang II stimulation, changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 77 publications
2
26
0
1
Order By: Relevance
“…These studies showed that Ang II induces NF-κB /RelA activation in VSMCs by increasing the relative abundance of phospho-Ser-536 RelA in the nucleoplasmic pool. We also confirmed Ang II-induced enhanced phospho-Ser-536 RelA formation in rat aortas treated with Ang II, establishing relevance to vascular signaling in vivo (Choudhary, et al, 2007;Cui, et al, 2006). Our group further showed that Ang II-induced RelA Ser-536 phosphorylation is mediated by NF-κB-inducing kinase (NIK), the major regulated step controlling non-canonical NF-κB signaling.…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcssupporting
confidence: 68%
See 2 more Smart Citations
“…These studies showed that Ang II induces NF-κB /RelA activation in VSMCs by increasing the relative abundance of phospho-Ser-536 RelA in the nucleoplasmic pool. We also confirmed Ang II-induced enhanced phospho-Ser-536 RelA formation in rat aortas treated with Ang II, establishing relevance to vascular signaling in vivo (Choudhary, et al, 2007;Cui, et al, 2006). Our group further showed that Ang II-induced RelA Ser-536 phosphorylation is mediated by NF-κB-inducing kinase (NIK), the major regulated step controlling non-canonical NF-κB signaling.…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcssupporting
confidence: 68%
“…In addition, RhoA inhibition also blocked Ang II-induced IL-6 expression, indicating that Ang II-inducible phospho-Ser-536 RelA was required for IL-6 activation (Cui, et al, 2006). Our studies in Ang II-stimulated VSMCs further showed that total RelA binding did not change on the native IL-6 promoter in response to Ang II, but fractional binding of phospho-Ser-536 RelA to the IL-6 promoter was increased (Choudhary, et al, 2007). These studies showed that Ang II induces NF-κB /RelA activation in VSMCs by increasing the relative abundance of phospho-Ser-536 RelA in the nucleoplasmic pool.…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcsmentioning
confidence: 48%
See 1 more Smart Citation
“…In these cells, substantial levels of RelA are found inactive in the nucleus under resting conditions. Ang II stimulation induces a pathway of RhoA and NIK activation, culminating in NIK-dependent phosphorylation of the nuclear RelA species on serine 536 (Choudhary et al, 2007;Cui et al, 2006). This phosphorylated pool of RelA is free from IB regulation and dynamically cycles through the nucleus, interacting with target genes (Bosisio et al, 2006;Sasaki et al, 2005).…”
Section: Gpcr Dependent Nf-κb Signalingmentioning
confidence: 99%
“…No entanto, a Ang II induz a transcrição do NF-kB através de uma via independente da proteólise de IkB, mas mediada por pequenas GTPases Rac/Rho A, exigida pelo complexo NIK-Rel A e induzindo a fosforilação phospho-ser-536 Rel A (Han et al, 1999). Desse modo, a ativação NFkB/Rel A ocorre através do aumento nos níveis de phospho-ser-536 Rel A no núcleo, essa resposta já foi observada aorta de ratos tratados com Ang II (Choudhary, et al, 2007;Cui, et al, 2006). Quando ativado pela Ang II, o NF-kB estimula a expressão de IL-6 por fibroblastos da adventícia, monócitos recrutados e CMLVs (Han et al, 1999).…”
Section: Mediadores De Inflamação Em CMLV Estimuladas Com Ang Iiunclassified